Transthyretin amyloid cardiomyopathy: 2025 update ; current diagnostic approaches and emerging therapeutic options - Tschöpe, Carsten; Elsanhoury, Ahmed; Kristen, Arnt (Journal of Clinical Medicine, 2025)
Transthyretin-related (ATTR) amyloidosis is a progressive, multisystem disease caused by the extracellular deposition of misfolded transthyretin (TTR)...